Horace on Terence (Epist. 2,1,59) - Adkin, Neil (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In Horace’s Epistle to Augustus the estimate of Terence may be less positive than is generally believed. This reinterpretation is based first on classical views of acoustic concinnity, then on etymological considerations.